Implementasi Undang-Undang No 5 Tahun 2018 tentang Terorisme Melalui Penguatan Moderasi Beragama - Agus Purnomo; Kardi Kardi (Justicia Islamica, 2023)
This article aimed to find the form of the role of strengthening religious moderation in implementing Law No. 5 of 2018 concerning Terrorism, considering that the two have overlapping focuses. This paper is based on field research conducted at two State Islamic Higher Education (PTKIN) that feature religious moderation programs. The approach taken in this research was legal sociology, precisely legal effectiveness. As a result, the form of strengthening religious moderation carried out by PTKIN in preventing radicalism, which is part of combating terrorism, has not played a significant role. Differences in the conditions of the regions where PTKIN is located are insufficient to differentiate the programs to enhance religious moderation. Therefore they have no implications for the role performed in preventing the notion of radicalism, particularly terrorism. Factors that create obstacles to implementing Law No. 5 of 2018 through strengthening religious moderation are aspects of the legal structure and legal substance.